1998
DOI: 10.1152/ajplung.1998.274.2.l235
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar liquid clearance in the anesthetized ventilated guinea pig

Abstract: Alveolar liquid clearance was examined in ventilated, anesthetized guinea pigs. An isosmolar 5% albumin solution was instilled into the lungs. Alveolar liquid clearance was studied over 1 h and was measured from the increase in alveolar protein concentration as water was reabsorbed. Basal alveolar liquid clearance was 38% of instilled volume. The high basal alveolar liquid clearance was not secondary to endogenous catecholamine release. Compared with control animals, epinephrine and the general β-adrenergic ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 30 publications
5
99
1
Order By: Relevance
“…Previous studies (17,34,35) demonstrated that before birth, preterm amiloride sensitivity is close to 100% because there seem to exist few or no other pathways for Na ϩ absorption. During normal lung development, amiloride does not affect lung fluid secretion at 61 days gestation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies (17,34,35) demonstrated that before birth, preterm amiloride sensitivity is close to 100% because there seem to exist few or no other pathways for Na ϩ absorption. During normal lung development, amiloride does not affect lung fluid secretion at 61 days gestation.…”
Section: Discussionmentioning
confidence: 99%
“…The other four guinea pigs remained anesthetized until the 1-h experimental time had passed and were then killed, and samples were obtained. At this time, a blood sample was obtained for FD70 analysis, and the lungs were collected for determination of extravascular plasma equivalents as previously described (31,34,40,46). Trichloroacetic acid (TCA) precipitation of plasma and urine samples verified that the FITC label (Ͼ97%) remained bound to the dextran tracer throughout the experimental time period.…”
Section: Endothelial and Epithelial Protein Permeabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Although significant efforts have been made to pharmacologically up-regulate alveolar fluid clearance to reverse the progression of lung injury, these approaches have not been successful (4). ␤ 2 -Adrenergic receptor (␤ 2 AR) agonists have been shown to enhance alveolar epithelial fluid transport via a cAMP-dependent mechanism under physiological conditions (5)(6)(7)(8)(9)(10)(11) and in various experimental models of ALI (12)(13)(14) as well as in one small prospective study in ALI patients (15). However, one of the main limitations of this therapeutic approach is that ␤-adrenergic agonist hyporesponsiveness has been reported in some experimental models of ALI (16,17), although none of the critical mediators of ALI have yet been shown to inhibit the ␤-adrenergic-stimulated fluid transport of the distal lung epithelium.…”
Section: Acute Lung Injury (Ali)mentioning
confidence: 99%